Pengaruh Intervensi Konseling Feeding Rules dan Massage Eating Difficulties terhadap Status Gizi pada Balita Stunting: The Effect of Feeding Rules and Massage Eating Difficulties Counseling Interventions on the Nutritional Status of Stunting Toddlers - Qomariyah; Desi Soraya; Linda Pramusinta (Universitas Ngudi waluyo, 2024)
Implementation of balanced nutrition during the pregnancy period and nutritional care patterns, especially in the first 1000 days of life, will influence the incidence of stunting in toddlers. Apart from that, the mother's health status plays an important role in determining the nutritional and health status of toddlers. To analyze the effect of counseling interventions on feeding rules and massage eating difficulties on the nutritional status of stunted toddlers. This type of research uses a quasi-experimental study in the form of a non-equivalent control group design carried out on toddlers aged 24 – 59 months based on measurements carried out by midwives in the Karangayu Community Health Center and Krobokan Community Health Center areas. This research was carried out using a consecutive sampling method, with a total sample of 40 subjects of toddlers whose nutritional status was seen from the WAZ, HAZ, and WHZ scores. The results of the difference test for WAZ, HAZ, and WHZ scores in the control group of 20 respondents showed that based on WAZ pre - WAZ post 1 with a value of p = 0.922, there were no different values. WAZ pre - WAZ post 2 found no different values. p = 0.101, there were no different values. WHZ pre – WHZ post 2 with a value of p = 0.002, it was found that there were different values. In the test of differences in WAZ, HAZ, and WHZ scores in the control group of 20 respondents, it showed that based on WAZ pre - WAZ post 1, the p-value = 0.469, there was no difference. WAZ pre - WAZ post 2, the p-value = 0.000, there was a difference value. pre – HAZ post 1, with a value of p = 0.043, there is a different value. HAZ pre – HAZ post 2, with a value of p = 0.000, there is a different value. post 2 with a p-value = 0.007, it was found that there were different values. It can be concluded that there are differences in the nutritional status of children aged 24-59 months between before and after being given counseling on feeding rules and massage eating difficulties for 3 months at Karangayu Community Health Center, Krobokan Community Health Center, and Pelita Shelter Home, seen from 20 respondents in the intervention group, WAZ pre - WAZ was obtained. post 1 has no different values, WAZ pre -WAZ post 2 has no different values, HAZ pre – HAZ post 1 has different values, HAZ pre – HAZ post 2 has different values and WHZ pre – WHZ post 1 has no different values, WHZ pre - WHZ post 2 there are different values. Meanwhile, in the control group of 20 respondents, it was found that WAZ pre - WAZ post 1 had no different values, WAZ pre - WAZ post 2 had different values, HAZ pre - HAZ post 1 had different values, HAZ pre – HAZ post 2 have different values and WHZ pre – WHZ post 1 have different values, WHZ pre – WHZ post 2 have different values. Abstrak Penerapan gizi seimbang selama periode kehamilan dan pola asuh gizi terutama dalam 1000 Hari Pertama Kehidupan akan memengaruhi kejadian stunting pada balita. Selain itu, status kesehatan ibu berperan penting dalam menentukan status gizi dan kesehatan balita. Untuk menganalisis pengaruh intervensi konseling feeding rules dan massage eating difficulties terhadap status gizi pada balita stunting. Jenis penelitian ini menggunakan studi quasi experiment berupa non equivalent control group design yang dilakukan pada balita usia 24 – 59 bulan yang berdasarkan pengukuran yang dilakukan oleh Bidan di wilayah Puskesmas Karangayu dan Puskesmas krobokan. Dalam penelitian ini dilakukan dengan metode consecutive sampling, dengan jumlah sampel 40 subyek terhadap balita yang status gizi dilihat dari skor WAZ, HAZ, dan WHZ. Hasil pada uji beda skor WAZ, HAZ, dan WHZ pada kelompok kontrol dari 20 responden menunjukkan berdasarkan WAZ pre – WAZ post 1 dengan nilai p = 0,922 didapatkan tidak ada nilai beda. WAZ pre – WAZ post 2 didapatkan tidak ada nilai beda.HAZ pre – HAZ post 1 nilai p = 0,009 didapatkan ada nilai beda.HAZ pre – HAZ post 2 nilai p = 0,012 didapatkan ada nilai beda.WHZ pre – WHZ post 1 dengan nilai p = 0,101 didapatkan tidak ada nilai beda. WHZ pre – WHZ post 2 dengan nilai p = 0,002 didapatkan ada nilai beda. Pada uji beda skor WAZ, HAZ, dan WHZ pada kelompok kontrol dari 20 responden menunjukkan berdasarkan WAZ pre – WAZ post 1 nilai p = 0,469 didapatkan tidak ada nilai beda.WAZ pre – WAZ post 2 nilai p = 0,000 didapatkan ada nilai beda.HAZ pre – HAZ post 1 nilai p = 0,043 didapatkan ada nilai beda.HAZ pre – HAZ post 2 dengan nilai p = 0,000 didapatkan ada nilai beda.WHZ pre – WHZ post 1 dengan nilai p = 0,027 didapatkan ada nilai beda.WHZ pre – WHZ post 2 dengan nilai p = 0,007 didapatkan ada nilai beda. Dapat disimpulkan terdapat perbedaaan status gizi anak usia 24-59 bulan antara sebelum dan sesudah diberi konseling feeding rules dan massage eating difficulties selama 3 bulan di Puskesmas Karangayu, Puskesmas Krobokan dan Rumah Singgah Pelita, dilihat dari 20 responden pada kelompok inteervensi didapatkan WAZ pre – WAZ post 1 tidak ada nilai beda, WAZ pre -WAZ post 2 tidak ada nilai beda, HAZ pre – HAZ post 1 ada nilai beda, HAZ pre – HAZ post 2 ada nilai beda dan WHZ pre – WHZ post 1 tidak ada nilai beda, WHZ pre – WHZ post 2 ada nilai beda.Sedangkan pada responden kelompok kontrol dari 20 responden didapatkan WAZ pre – WAZ post 1 tidak ada nilai beda, WAZ pre – WAZ post 2 ada nilai beda, HAZ pre – HAZ post 1 ada nilai beda, HAZ pre – HAZ post 2 ada nilai beda, dan WHZ pre – WHZ post 1 ada nilai beda, WHZ pre – WHZ post 2 ada nilai beda.